2019
DOI: 10.1111/ijn.12801
|View full text |Cite
|
Sign up to set email alerts
|

Illness perceptions among patients with type 2 diabetes mellitus: A cross‐sectional study

Abstract: Aims: This study aimed to investigate illness perceptions and their predictors among Chinese patients with type 2 diabetes. Methods: A descriptive, correlational, and exploratory design was used. The Chinese version of the Revised Illness Perception Questionnaire was modified and used to collect data between September 2016 and February 2017. Results: On average, patients recognized fewer than five of the 14 common symptoms of type 2 diabetes. Of the six causal factors, "dietary behaviours" had the highest mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 28 publications
4
15
0
2
Order By: Relevance
“…In addition, the severity of complications may negatively influence illness perception and this population was composed of inpatients requiring comprehensive treatment. Alternatively, these patients demonstrated high levels of self-control and treatment control, consistent with previous studies [ 7 , 10 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, the severity of complications may negatively influence illness perception and this population was composed of inpatients requiring comprehensive treatment. Alternatively, these patients demonstrated high levels of self-control and treatment control, consistent with previous studies [ 7 , 10 ].…”
Section: Discussionsupporting
confidence: 90%
“…Inappropriate perception of illness can lead to psychological disorders [ 7 ], and a recent study found that maladaptive illness perception was directly associated with depression in diabetes patients [ 8 ]. However, few studies have examined illness perception among T2DM patients in China [ 9 , 10 ], and even less attention has been paid to the potential mechanisms underlying the relationship between illness perception and depression.…”
Section: Introductionmentioning
confidence: 99%
“…These findings have been supported by subsequent research that found lower HbA 1c was associated with perceived personal control over diabetes 12,13 and more chronic timeline perceptions 14 . Illness perceptions associated with higher HbA 1c include greater consequences, 13 stronger illness identity, 13,15 more cyclical timeline beliefs 4,16 and greater emotional distress 13 …”
Section: Introductionmentioning
confidence: 62%
“…In contrast, parents in cities are more educated, with better medical insurance, more medical resources and higher family income, as well as a better understanding of the tumor. Moreover, they are better at understanding and dealing with family nursing and medical treatment, which is more conducive to family stability and doctor-patient cooperation [13]. Healthcare staff should care more about the parents with low income and educational level in remote areas, help the parents and other family members to learn more about the disease, and encourage the families to support and participate in the family nursing of children, so as to strengthen family bonds.…”
Section: Maintaining Family Integration Cooperation and An Optimisticmentioning
confidence: 99%